Association between right heart size and right ventricular output reserve in patients with pulmonary arterial hypertension - Egenlauf, Benjamin; Weinstock, K. F.; Marra, A. M.; Eichstaedt, Christina; Harutyunova, Satenik; Grünig, Ekkehard; Xanthouli, Panagiota; Benjamin, Nicola (International journal of cardiology, 2024)
Objectives - Right ventricular (RV) output reserve, defined as increase of cardiac output during exercise, is reduced in patients with pulmonary arterial hypertension (PAH). Aim of this study was to evaluate the association of right heart size measured by echocardiography and invasively measured RV function at rest and during exercise in PAH patients. - Methods - Adult PAH-patients who received routine haemodynamic assessment at rest and during exercise by right heart catheterisation and echocardiographic measurement of right heart size (right atrial (RA) and RV area) were included in this study. Clinical, echocardiographic, laboratory, exercise and invasive haemodynamic parameters were retrospectively analysed. The primary endpoint was to assess the association between right heart size and right ventricular function. - Results - Data from 215 PAH patients (age 58.9 ± 15.9 years, 63.3% female, 62.2% double or triple combination treatment) were analysed in this cross-sectional study. Cardiac index was significantly lower for patients with enlarged RA-area > 18 cm2 at rest, and at 25 and 50 W (all p < 0.001) and for patients with enlarged RV area > 20 cm2 at rest, 25, 50 and 75 W (all p < 0.001). Furthermore, pulmonary vascular resistance and mPAP/CO slope (all p < 0.001) were significantly higher and pulmonary arterial compliance (all p < 0.05) was significantly lower in patients with enlarged RA or RV area. RA and RV area correlated with TAPSE/sPAP (both p < 0.001, R − 0.570 and − 0.530). - Conclusion - This study could underline that an enlargement of RA- and RV-area is associated with an impaired RV function at rest and during exercise in patients with PAH.
Online verfügbar 17 August 2024, Version des Artikels 30 August 2024
Gesehen am 21.02.2025